Endogenous carbamylation of renal medullary proteins. - J'Neka S Claxton; Pablo C Sandoval; Gary Liu; Chung-Lin Chou; Jason D Hoffert; Mark A Knepper (PLoS ONE)
Protein carbamylation is a post-translational modification that can occur in the presence of urea. In solution, urea is in equilibrium with ammonium cyanate, and carbamylation occurs when cyanate ions react with the amino groups of lysines, arginines, protein N-termini, as well as sulfhydryl groups of cysteines. The concentration of urea is elevated in the renal inner medulla compared with other tissues. Due to the high urea concentration, we hypothesized that carbamylation can occur endogenously within the rat inner medulla. Using immunoblotting of rat kidney cortical and medullary homogenates with a carbamyl-lysine specific antibody, we showed that carbamylation is present in a large number of inner medullary proteins. Using protein mass spectrometry (LC-MS/MS) of rat renal inner medulla, we identified 456 unique carbamylated sites in 403 proteins, including many that play important physiological roles in the renal medulla [Data can be accessed at https://helixweb.nih.gov/ESBL/Database/Carbamylation/Carbamylation_peptide_sorted.html]. We conclude that protein carbamylation occurs endogenously in the kidney, modifying many physiologically important proteins.